Global geno-proteomic analysis reveals cross-continental sequence conservation and druggable sites among influenza virus polymerases - Babar, Mustafeez Mujtaba; Zaidi, Najam-us-Sahar Sadaf; Tahir, Muhammad (Antiviral research, 2014)
•Polymorphism analyses reveal 12% and 6% conservation among viral polymerase nucleotide and protein sequences resp.•Identified 29 conserved nucleotide regions can potentially be targeted for inhibitor designing.•Polymerases have undergone purifying mutations over past 6 decades resulting in their steady molecular existence.•Based on continent-based host classification, a consistent geo-phylogenetic pattern is observed.•Conserved protein regions and drug pockets on polymerases indicate their preference for druggability. Influenza virus is one of the major causes of mortality and morbidity associated with respiratory diseases. The high rate of mutation in the viral proteome provides it with the ability to survive in a variety of host species. This property helps it in maintaining and developing its pathogenicity, transmission and drug resistance. Alternate drug targets, particularly the internal proteins, can potentially be exploited for addressing the resistance issues. In the current analysis, the degree of conservation of influenza virus polymerases has been studied as one of the essential elements for establishing its candidature as a potential target of antiviral therapy. We analyzed more than 130,000 nucleotide and amino acid sequences by classifying them on the basis of continental presence of host organisms. Computational analyses including genetic polymorphism study, mutation pattern determination, molecular evolution and geophylogenetic analysis were performed to establish the high degree of conservation among the sequences. These studies lead to establishing the polymerases, in particular PB1, as highly conserved proteins. Moreover, we mapped the conservation percentage on the tertiary structures of proteins to identify the conserved, druggable sites. The research study, hence, revealed that the influenza virus polymerases are highly conserved (95–99%) proteins with a very slow mutation rate. Potential drug binding sites on various polymerases have also been reported. A scheme for drug target candidate development that can be employed to rapidly mutating proteins has been presented. Moreover, the research output can help in designing new therapeutic molecules against the identified targets.